Effects Of Green Marketing, E-Wom, And Brand Image On Purchase Intention Through Consumer Education/Learning: Evidence From Starbucks Reserve Dewata Bali - Zelamewani, Ni Kadek Resy; Karta, Ni Luh Putu Agustini; Mekarini, Ni Wayan (Jurnal Edukasi, 2025)
This study aims to analyze the effect of green marketing, electronic word of mouth (E-WOM), and brand image on purchase intention, both partially and simultaneously, in the case of Starbucks Reserve Dewata Bali. The phenomenon underlying this research is the growing awareness of environmental sustainability that shapes modern consumer behavior, especially in the premium coffee industry. Data were collected from 140 respondents who were consumers of Starbucks Reserve Dewata Bali using a questionnaire distributed via purposive sampling. The study applied descriptive quantitative methods with multiple linear regression analysis to test the hypotheses. The findings indicate that green marketing, E-WOM, and brand image each have a positive and significant effect on purchase intention. Simultaneously, the three variables contribute significantly to strengthening consumers’ intention to purchase. Green marketing strategies focusing on sustainability, positive consumer reviews shared digitally, and a strong, trusted brand image collectively reinforce consumers' purchase decisions. The study concludes that integrating environmental, social, and digital communication aspects into marketing strategies is crucial for enhancing purchase intention in environmentally conscious markets. These results provide managerial implications, suggesting that businesses, particularly in the premium coffee sector, should continuously strengthen sustainability practices, digital engagement, and brand positioning to remain competitive and relevant.